Vasopressin in Heart Failure - Iovino, Michele; Iacoviello, Massimo; De Pergola, Giovanni; Licchelli, Brunella; Iovino, Emanuela; Guastamacchia, Edoardo; Giagulli, Vito A.; Triggiani, Vincenzo (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2018)
Background and Objective: The nonapeptide hypothalamic hormone vasopressin (VP), exerts important effects on cardiovascular system via its receptors V1, V2 and V3. Patients with congestive heart failure (CHF) present elevated plasma VP levels. Aim of this paper is to review the role of vasopressin in CHF. Methods: We analyzed the best of published literature dealing with the role of VP in patients affected by CHF, identifying keywords and MeSH terms in Pubmed and then searching them. The last search was performed on August 2017. Results: Scientific articles dealing with the relationship between VP and CHF show that circulating high VP levels found in CHF despite an exaggerated increase in circulatory blood volume can contribute to CHF exacerbation. In particular, the stimulation of V1R induces vascular constriction responsible for increased systemic vascular resistance and afterload, and, in addition, coronary vasoconstriction with consequent reduced coronary circulation and cardiac contractility, whereas the stimulation of V2R induces free water reabsorption and this is responsible of preload increase and congestion of pulmonary vascular bed with edema and hyponatremia, markers of advanced CHF. Conclusion: VP can play an important role among the derangements of the endocrine system in CHF even being a possible target in the treatment of this condition. Vaptans, antagonists of VP receptors, in fact, are able to increase urine output and plasma sodium levels without the increased risk of arrhythmic death induced by diuretics, even though, further studies are needed to establish a possible role of these drugs in the treatment of CHF.
Keywords: vaptans